Reporte de caso clínico, hiperqueratinizacion con dextrosa al 50% en pacientes edéntulo con tejido blando hipermóvil en las clínicas odontológicas UAN Ibagué. (2020)
Introduction. Hypermobile soft tissue -TBH has a prevalence of 24% in the upper jaws and 5% in the lower jaws. Barón, J. et al., Reported fibrosis in the connective tissue of the vestibular mucosa after infiltrations with 50% dextrose in the mucosa. Oral in experimental animals. The purpose of this clinical case was to evaluate hyperkeratinization with 50% dextrose infiltration in an edentulous patient with hypermobile soft tissue. Materials and methods. Case report. An 80-year-old female patient comes to the clinic at the Odontology Clinic of the Antonio Nariño University Ibagué Campus, where a comprehensive diagnosis, prognosis and treatment plan are made. The patient presented TBH in the anterosuperior sector, a punch biopsy was performed before and after 20 minutes of the 50% dextrose infiltration procedure for the first time a week, and for the second time, at seven weeks, with monitoring. Every eight days and laboratory tests with range within normal limits. It complies with resolution number 008430 of 1993, an investigation considered to have a greater than minimum risk. Results. Diagnosis Fibroepithelial hyperplasia with dysplastic hyperkeratosis where high vascularization indicates epithelial regeneration as an adequate therapeutic response. Conclusions. The use of osmotic agents induce an inflammatory response, releasing cytokines and growth factors that induce tissue recovery. An excellent post-surgical evolution was observed and a treatment plan aimed at the rehabilitation of the patient was established.